2009
DOI: 10.1021/jf901614y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the Dihydrochalcone Aspalathin Leads to Dimerization

Abstract: Aspalathin and nothofagin are typical ingredients of unfermented rooibos (Krafczyk, N.; Glomb, M. A. J. Agric. Food Chem. 2008, 56, 3368). During oxidation these dihydrochalcones were degraded to higher molecular weight browning products under aerated and nonenzymatic conditions. In the early stages of browning reactions aspalathin formed two dimers. These two compounds were unequivocally established as atropisomers stemming from oxidative A to B ring coupling. Multilayer countercurrent chromatography (MLCCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
2
33
0
1
Order By: Relevance
“…On the other hand, unfermented rooibos tea, known as "green rooibos tea", has been the focus of research because it contains higher levels of flavonoids and polyphenols than fermented rooibos tea, in which flavonoids and polyphenols are degraded and form dimers by oxidation during the fermentation process (Krafczyk et al, 2009, Heinrich et al, 2012. In particular, aspalathin (Asp), a major flavonoid in rooibos, is present at twice the level in unfermented compared to fermented tea (Bramati et al, 2002, Bramati et al, 2003.…”
Section: Rooibos (Aspalathus Linearis) Is a Leguminous Shrub Native Tomentioning
confidence: 99%
“…On the other hand, unfermented rooibos tea, known as "green rooibos tea", has been the focus of research because it contains higher levels of flavonoids and polyphenols than fermented rooibos tea, in which flavonoids and polyphenols are degraded and form dimers by oxidation during the fermentation process (Krafczyk et al, 2009, Heinrich et al, 2012. In particular, aspalathin (Asp), a major flavonoid in rooibos, is present at twice the level in unfermented compared to fermented tea (Bramati et al, 2002, Bramati et al, 2003.…”
Section: Rooibos (Aspalathus Linearis) Is a Leguminous Shrub Native Tomentioning
confidence: 99%
“…Following fractionation of an HPLC eluate of an ethyl acetate fraction of fermented rooibos and incubation of the fractions to measure color formation (absorbance at 450 nm based on maximum absorbance for fermented rooibos), aspalathin was identified as the most important substrate for the formation of colored products (Krafczyk et al, 2009a). Incubation of aspalathin under aerated and deaerated conditions confirmed that the browning reaction is oxygen-dependent.…”
Section: Effects Of Production and Processingmentioning
confidence: 90%
“…Beelders et al (2012b) studied the composition of hotwater infusions of both fermented and green rooibos, identifying 28 compounds of which all, except for the C5′-hexosyl derivative of aspalathin, have been previously identified in fermented rooibos. The oxidation mechanism of aspalathin, as recently elucidated by Glomb and co-workers (Krafczyk and Glomb, 2008;Krafczyk et al, 2009a;Heinrich et al, 2012), will be discussed in the section Processing of Fermented Rooibos and Oxidative Conversion of Aspalathin, below. It is a novel compound and its structure suggests that it may be an oxidation product formed during fermentation.…”
Section: Phenolic Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…Weder Eriodictyole, Isoorientin, Orientin, noch die Dimere sind jedoch gefärbte Substanzen. Sie stellen lediglich Intermediate innerhalb der Fermentationskaskade dar, und werden im weiteren Verlauf zu braunen Melaninen abgebaut .…”
Section: Enzymatische Bräunung Von Echtem Tee (Camellia Sinensis)unclassified